2008
DOI: 10.1016/j.str.2007.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Close Correspondence between the Motions from Principal Component Analysis of Multiple HIV-1 Protease Structures and Elastic Network Modes

Abstract: The large number of available HIV-1 protease structures provides a remarkable sampling of conformations of the different conformational states, which can be viewed as direct structural information about the dynamics of the HIV-1 protease. After structure matching, we apply principal component analysis (PCA) to obtain the important apparent motions for both bound and unbound structures. There are significant similarities between the first few key motions and the first few low-frequency normal modes calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
190
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(211 citation statements)
references
References 38 publications
21
190
0
Order By: Relevance
“…5c). The lowest and second lowest frequency modes calculated by normal mode analysis 42 corresponded to similar motions in the molecule than the first and second PC, as typically found with other biomolecules 43 .…”
Section: Saxs Experimentssupporting
confidence: 68%
“…5c). The lowest and second lowest frequency modes calculated by normal mode analysis 42 corresponded to similar motions in the molecule than the first and second PC, as typically found with other biomolecules 43 .…”
Section: Saxs Experimentssupporting
confidence: 68%
“…66 It is also possible to use a set of experimental structures in different liganded complexes (if they are available) to compute the binding induced dynamics. [67][68][69][70] The recent study of Bakan and Bahar has shown that ENM predicted modes are very well correlated with the principal components of the conformational change for a large set of different liganded experimental structures of a given protein. 71 We have repeated the same analysis for our test protein: PDZ domain.…”
Section: Elastic Network Model and Generating New Conformations Usingmentioning
confidence: 95%
“…Overlap between ANM modes and PCs is evaluated using the correlation cosine between the eigenvectors, 51,52 …”
Section: Overlap Between Anm Modes and Pcsmentioning
confidence: 99%